Strong photo-response in a flip-chip nanowire p-Cu2O/n-ZnO junction - Deo, Meenal S.; Mujawar, Sarfraj; Game, Onkar S.; Yengantiwar, Ashish; Banpurkar, Arun G.; Kulkarni, Sneha; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Nanoscale, 2011)
Cu2O nanoneedles are synthesized on a copper substrate by a simple anodization and reducing ambient annealing protocol. ZnO nanorods are grown on ITO coated glass by a low temperature chemical route. The electronic and photo-response properties of the p-Cu2O/n-ZnO flip-chip heterojunction are then studied and analyzed. We show that the I-V characteristic is rectifying and the junction exhibits a good photoresponse (similar to 120% under 1 V reverse bias) under AM 1.5 (1 Sun) illumination. This nano-heterojunction photo-response is far stronger as compared to that of a pulsed laser deposited thin film p-Cu2O/n-ZnO heterojunction, which can be attributed to higher junction area in the former case.

Solution chemistry-based nano-structuring of copper dendrites for efficient use in catalysis and superhydrophobic surfaces - Bakthavatsalam, Rangarajan; Ghosh, Subrata; Biswas, Ratul Kumar; Saxena, Aayushi; Raja, Alagar; Thotiyl, Musthafa Ottakam; Wadhai, Sandip; Banpurkar, Arun G.; Kundu, Janardan (RSC Advances, 2016)
Despite their performance and economic advantages over Ag and Au, there have been no focused research efforts on the nano-structuring of Cu dendrites with respect to fine-tuning their structure/morphology towards the efficiency enhancement of suitable applications. Reported here is a simple, versatile, environmentally-friendly and galvanic replacement reaction-based solution chemistry methodology to synthesize highly nano-structured copper dendrites targeted towards the efficiency enhancement of desired applications. Herein, copper is deposited galvanically on an Al foil in the presence of NaCl/HCl, wherein the chloride anions augment an uninterrupted replacement reaction. The growth process of Cu dendrites has been probed in detail. The presence of acid, the type of Cu2+ precursor salt, the Cu2+ ion concentration, the surfactant concentration and the reaction temperature are all demonstrated to provide useful means of modulating the surface structure/morphology of the dendrites. Notably, dendrites formed in the presence of acid are found to be highly nano-structured. Moreover, it is also found that the morphology/structure of the obtained Cu deposit depends considerably upon the choice of the Cu2+ precursor salt, a parameter that has been completely overlooked in the past. The acid-induced nano-structuring of the dendrites is exploited for enhancing their efficiency in the catalytic reduction of para-nitrophenol and for fabricating self-cleaning superhydrophobic surfaces. These nano-structured dendrites are demonstrated to have the highest ever normalized rate constant for the catalytic reduction reaction. Superhydrophobic surfaces fabricated using these dendrites demonstrate excellent self-cleaning abilities, showing a high contact angle (159 degrees) with low contact angle hysteresis (2 degrees). This facile synthetic strategy for the fabrication of highly nano-structured Cu dendrites is expected to open up avenues for the production of Cu-based low-cost functional nano/micro-materials.